IMPROVING TEACHERS’ SKILLS IN DESIGNING HOTS (HIGHER ORDER THINKING SKILLS) QUESTIONS THROUGH TEACHER WORK GROUP (KKG) - Hiliyati Yus (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The quality of teachers as educators becomes an important factor, one of which is the quality in designing HOTS (Higher Order Thinking Skills) questions. This study aimed to improve teachers’ ability in designing HOTS (Higher Order Thinking Skills) questions through teacher work group (KKG). The subjects of this study were 26 teachers. This study was conducted by using school action research methods conducted in several cycles. The results demonstrated an increase in teachers’ activities in the first cycle; the average percentage was 73% with a good category. Then, the average percentage in the second cycle was 91% with a very good category. It was also found that the average score of teachers’ ability in designing HOTS questions in the first cycle was 80.76 with good category, while the average score in the second cycle was 96.92 with the very good category. Hence, it can be concluded that carrying out KKG activities was effective to increase the teachers’ ability in designing HOTS questions.